Electrocatalysis of oxygen reduction on iron- and cobalt-containing nitrogen-doped carbon nanotubes in acid media. (10th November 2016) - Ratso, Sander; Kruusenberg, Ivar; Sarapuu, Ave; Kook, Mati; Rauwel, Protima; Saar, Rando; Aruväli, Jaan; Tammeveski, Kaido
Highlights: M-NCNT materials are synthesised by pyrolysis of CNTs, DCDA and FeCl3 or CoCl2 . As-prepared M-NCNT catalysts show lower ORR activity than Pt/C in acid solution. ORR activity increases by acid-treatment of M-NCNT catalysts and second pyrolysis. The prepared M-NCNT electrocatalysts show high stability and methanol tolerance. Abstract: Iron- and cobalt-containing nitrogen-doped carbon catalysts based on multi-walled carbon nanotubes are prepared using pyrolysis of dicyandiamide and CoCl2 or FeCl3 at 800 °C. The electroreduction of oxygen is studied in 0.5 M H2 SO4 solution by the rotating disk electrode method and the surface morphology and composition of the catalysts are characterised by scanning and transmission electron microscopies and X-ray photoelectron spectroscopy. The as-prepared catalysts show mediocre electrocatalytic activity for oxygen reduction reaction (ORR), which increases as a result of acid treatment and second pyrolysis. The electrocatalytic activity of Fe-containing catalyst towards the ORR surpasses that of Co-based material and it supports a 4-electron reduction of O2 . Co-containing catalyst, in turn, shows higher stability. Both catalysts are highly methanol tolerant in acid media. The transition metal-containing N-doped carbon materials are promising cathode catalysts for low-temperature fuel cells.